Frequency of Gluten-Reactive T Cells in Active Celiac Lesions Estimated by Direct Cell Cloning - Qiao, Shuo-Wang; Dahal-Koirala, Shiva; Eggesbø, Linn M.; Lundin, Knut E. A.; Sollid, Ludvig M. (Frontiers in Immunology, 2021)
Chronic inflammation of the small intestine in celiac disease is driven by activation of CD4+ T cells that recognize gluten peptides presented by disease-associated HLA-DQ molecules. We have performed direct cell cloning of duodenal biopsies from five untreated and one refractory celiac disease patients, and three non-celiac disease control subjects in order to assess, in an unbiased fashion, the frequency of gluten-reactive T cells in the disease-affected tissue as well as the antigen fine specificity of the responding T cells. From the biopsies of active disease lesions of five patients, 19 T-cell clones were found to be gluten-reactive out of total 1,379 clones tested. This gave an average of 1.4% (range 0.7% - 1.9%) of gluten-reactive T cells in lamina propria of active celiac lesions. Interestingly, also the patient with refractory celiac disease had gluten-reactive T cell clones in the lamina propria (5/273; 1.8 %). In comparison, we found no gluten-reactive T cells in any of the total 984 T-cell clones screened from biopsies from three disease control donors. Around two thirds of the gluten-reactive clones were reactive to a panel of peptides representing known gluten T-cell epitopes, of which two thirds were reactive to the immunodominant DQ2.5-glia-α1/DQ2.5-glia-α2 and DQ2.5-glia-ω1/DQ2.5-glia-ω2 epitopes. This study shows that gluten-reactive T cells in the inflamed duodenal tissue are prevalent in the active disease lesion, and that many of these T cells are reactive to T-cell epitopes that are not yet characterized. Knowledge of the prevalence and epitope specificity of gluten-specific T cells is a prerequisite for therapeutic efforts that target disease-specific T cells in celiac disease.